Study Report of existing forensic tools and technologies to identify Darknet - Joshi, Preeti S; Dinesha, Dinesha H.A (International Journal of Computer Sciences and Engineering, 2025)
DarkNet is the portion of Internet that is intentionally kept hidden and is only accessible by special soft wares and non-standard communication protocols and ports. Accessing these portion is not illegal at all times, but these software make it possible to keep the user anonymous and preserve data privacy. Anonymous communication has gained popularity and is of much interest. Anonymity leads to compromising nonrepudiation and security goals. Apart from providing freedom of speech to user, anonymity also provides conducive environment to illegal activities and different kinds of cyber-attacks. Network surveillance and forensic investigation is required to reconstruct or collect evidence but becomes a challenge due to anonymity, encryption and newer ways of cyber-attack. Innovative methods and techniques are required for overcoming these challenges of DarkNet. Sniffing the network for information, traffic analysis, anomaly and intrusion detection are few techniques to find evidences. With a plethora of tools and techniques available for collecting, identifying, processing and analyzing data on the networks, we try to explore few tools for forensic investigation in the DarkNet